P1102EVALUATION THE EFFICACY OF MEDIUM CUT- OFF MEMBRANE DIALYZERS AND COMPARISON WITH HIGH FLUX DIALYZERS IN CONVENTIONAL HEMODIALYSIS - Rambabova Bushljetikj, Irena; Trajcheska, Lada; Pushevski, Vladimir; Biljali, Sefedin; Balkanov, Trajan (Oxford University Press (OUP), 2020)
Hemodialysis (HD) is the most widely used modality of renal replacement therapy. The high-flux dialyzers in standard hemodialysis offer numerous benefits for ESRD patients, such as, increasing the uremic toxins removal and improving patients survival, reduced patients admission and morbidity. A new class of membranes, medium cut-off (MCO) membranes, has been designed to achieve better removal capacities for middle and large middle molecules, as well as to ensure the retention of albumin in hemodialysis (HD) treatments. We evaluated the removal efficacy of Theranova® in standard HD in comparison with standard high- flux HD. Method Four stable HD patients (M/F 1/4) were included in 12-weeks small observational pilot study in HD with Theranova® 400 (sup. 1.7 m2) and Theranova® 500 (sup. 2.0 m2) dialyzers. Each patient was assessed four times, T0 with standard high flux dialyzers, T1 at 1 month, T2 at second month and T3 at third month, by measuring pre and post-HD samples of: urea, creatinine, beta2-microglobilin (B2M), myoglobin, albumin and FLC-k, FLC-λ . Data are reported as mean ± standard deviation (SD). The removal rates of uremic toxins are expressed as percentages. Results The average removal rates for the uremic toxins with standard high-flux membranes were 18.4% for B2M, 14.3% for Myoglobin, 19.8 % for FLC-k and 17.4 % for FLC-λ. The data showed a higher average removal rate for all the uremic toxins with Theranova® dialyzers for B2M, Myoglobin, FLC-k and FLC-λ (62.7%, 56.9%, 63.5%, 54.6%, respectively) during the 3 months of follow up. The using of Theranova® dialyzers in standard HD was enough to significantly decrease the pre-dialysis value of Urea (17.72 ± 2.26 vs 13.75 ± 3.75, p=0.001), Creatinine (700.50 ± 315.07 vs 570.00 ± 206.64, p=0.021), B2M (40.90 ± 11.00 vs 29.00 ± 4.64, p=0.005), FLC-k (267.25 ± 113.28 vs 225.25 ± 100.62, p=0.018), FLC-λ (324.25 ± 116.12 vs 215.23 ± 64.44, p=0.011), Myoglobin ( 199.96 ± 124.41 vs 137.00 ± 83.14, p= 0.049). Finally, albumin retention was observed with Theranova® dialyzers, between T0 and T3 it increased significantly (40.50 ± 4.79 vs 42.25 ± 4.50, p=0.0001). Conclusion Compared to high-flux dialysis membranes, novel medium cut-off (MCO) membranes show greater permeability for larger middle molecules in mid -term report. But the long term analysis and larger number of patients is necessary to evaluate a clinical significance of this innovative therapy.